KOMPOSISI DAN STRUKTUR JENIS POHON DI HUTAN PRODUKSI TERBATAS AKE OBA – TANJUNG WAYAMLI – AKE KOBE - Didi Kasmadi; Johny S. Tasirin; Maria Y.M.A. Sumakud (COCOS, 2015)
ABSTRACT  Limited Production Forest (HPT) Ake Oba - Tanjung Wayamli -Ake Kobe with an area reaching 151.603 ha. This area is divided into several districts / cities, one of which is the City of Tidore Islands with an area of about 26.707,5 ha. Collecting data in the field by the method of sample plots with a size of 100 mx 100 m with a total area of field observation area of 3 ha. From the data processing on field observation plots are 52 type of scientific names with 61 types based on local names with the number of individual trees of 678 individuals (including the level of seedlings, saplings, poles and trees). The most dominant type is the type of Hiru (Vatica papuana Dyer) as many as 102 individuals, K. Iron (Intsia bijuga O.Kt.Ze) as many as 70 individuals, Kora (Anisoptera polyandra Bl.) By 51 individuals, caplong (Calophyllum sp.) As 40 individuals and Kenari (Canarium balsamiferium Wild) as many as 35 individuals.  Keywords: Composition and Trees Structure, Sample Plot, HPT Ake Oba - Tanjung Wayamli -Ake Kobe.